2004
DOI: 10.1128/jb.186.14.4802-4807.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of Escherichia coli DNA Polymerase IV in In Vivo Replication Fidelity

Abstract: We have investigated whether DNA polymerase IV (Pol IV; the dinB gene product) contributes to the error rate of chromosomal DNA replication in Escherichia coli. We compared mutation frequencies in mismatch repair-defective strains that were either dinB positive or dinB deficient, using a series of mutational markers, including lac targets in both orientations on the chromosome. Virtually no contribution of Pol IV to the chromosomal mutation rate was observed. On the other hand, a significant effect of dinB was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 44 publications
7
70
0
Order By: Relevance
“…The overespression of the polymerase causes -1 frameshifts in polypurine runs of G in undamaged DNA [22]. When looking at spontaneous mutagenesis, previous studies have shown a statistically significant decrease in the number of frameshift and base substitution events in the absence of dinB [23,24,32] while overexpression of the dinB gene results in a significant increase in the mutation frequency [21,22]. Pol IV was chosen as a candidate to analyze for strand slippage within microsatellite alleles because a role for the polymerase in spontaneous mutagenesis was acknowledged, as was its role in mutagenesis at homoploymeric G sequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overespression of the polymerase causes -1 frameshifts in polypurine runs of G in undamaged DNA [22]. When looking at spontaneous mutagenesis, previous studies have shown a statistically significant decrease in the number of frameshift and base substitution events in the absence of dinB [23,24,32] while overexpression of the dinB gene results in a significant increase in the mutation frequency [21,22]. Pol IV was chosen as a candidate to analyze for strand slippage within microsatellite alleles because a role for the polymerase in spontaneous mutagenesis was acknowledged, as was its role in mutagenesis at homoploymeric G sequences.…”
Section: Discussionmentioning
confidence: 99%
“…A higher expression of Pol IV is detected from the F factor compared to expression from the chromosomal copy of the dinB gene [24]. Deletion of dinB from the chromosomal location has a negligible effect on mutagenesis [24]; however deletion from the episome produced a significant effect on mutagenesis [24,32]. Pol IV protein levels also are dependent on the growth phase of the culture.…”
Section: Pol IV and Hsv-tk Mutagenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Foster, Submitted for publication). However, loss of Pol IV has little effect on normal, growth-dependent mutation rates, although this also depends on the mutational target [13,15,16] (P.L. Foster, Submitted for publication).…”
Section: The Sos Responsementioning
confidence: 99%
“…This had appeared to be true when irrelevant genes, ilvG and rpoB, were monitored for mutation during lactose selection [35,38]. However, the target for Lac + reversion is on F, the conjugal plasmid, and mutation of genes on F appears to occur at a higher rate and by a different mechanism than mutation of genes on the chromosome [16,43,44]. When a second revertible allele, a +1 frameshift in the tetA gene, was on the episome close to the Lac − allele, TetR revertants appeared at about the same rate as did Lac + mutations during lactose selection.…”
Section: Adaptive Mutations Are Not Directedmentioning
confidence: 99%